1990
DOI: 10.3354/meps060211
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive aspects of meiobenthic copepod dispersal at two sites near I Mustang Island, Texas

Abstract: Dispersal of meiobenthic copepods was examined at 2 subtidal sites subject to moderate flow conditions, and in a laboratory experiment under conditions of no-flow. Small-scale spatial heterogeneity In settlement into containers filled with azoic sediment was found for several species in 3 field experiments. The species composition in the colonization containers was different from that observed in the surrounding sediments. Juvenile copepodites of several species were disproportionally abundant in the container… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
12
2
Order By: Relevance
“…Their study revealed that relative to adults, resuspension rates by late stage nauplii and all copepodite stages was infrequent. Contrary results obtained here and by Kern (1990) suggest that sediment abundance variability is indeed flow/body size interactive. Copepodites are the smallest postlarval individuals in the P. megarostrum population, with average body volumes about one-third that of adult females.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Their study revealed that relative to adults, resuspension rates by late stage nauplii and all copepodite stages was infrequent. Contrary results obtained here and by Kern (1990) suggest that sediment abundance variability is indeed flow/body size interactive. Copepodites are the smallest postlarval individuals in the P. megarostrum population, with average body volumes about one-third that of adult females.…”
Section: Discussioncontrasting
confidence: 54%
“…nematodes or copepods, or of individual species. Apart from Kern's (1990) investigation of the effects of subtidal flow fields on copepods near Mustang Island, Texas (USA) none has addressed what impact these variables might have on various life history categories within a species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, researchers have targeted the processes governing either movement into or settlement out of the water column, but not both (e.g. Armonies 1988a, Fegley 1988, Kern 1990, Walters 1991. Separate studies of copepod advection (Palmer & Gust 1985) and the colonization of defaunated sediments in hydrodynamically active habitats (Sherman & Coull 1980, Chandler & Fleeger 1983, Kern & Taghon 1986, Fegley 1988) suggest a direct connection between pelagic dispersal and benthic recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…sand versus seagrass; Hicks 1986). Within habitats, emergence may vary with food concentration, intraspecific density, and age composition (Service and Bell 1987;Kern 1990), the latter may in part derive from differential feeding habits of adults and juveniles (Decho and Fleeger 1988). Therefore, when including markedly different habitats some extra experiments should be done to check for habitat-specific differences in emergence.…”
Section: Modifications For Other Geographical Areas or Other Taxamentioning
confidence: 99%